2018
DOI: 10.1542/peds.2017-4274
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Associations of Parent Adverse Childhood Experiences and Child Health Outcomes

Abstract: The full scope of the health effects of ACEs may not be limited to the exposed individual, highlighting the need for a 2-generation approach to addressing the social determinants of child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 46 publications
4
92
0
2
Order By: Relevance
“…However, researchers have examined other parent traumas and health outcomes for their offspring, and those findings are congruent with ours. For example, children born to parents who were exposed to ACEs had worse physical (Lê-Scherban et al, 2018; Madigan et al, 2017) and mental health (Madigan et al, 2017) as well as inferior socioemotional (McDonnell and Valentino, 2016) and developmental outcomes (Lê-Scherban et al, 2018; Madigan et al, 2017; Sun et al, 2017). Additional work outside ACEs has shown that offspring born to parents who experienced trauma such as genocide or indentured child labor during childhood also had higher risk for psychopathology (Field et al, 2011; Kuffer et al, 2016; Roth et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers have examined other parent traumas and health outcomes for their offspring, and those findings are congruent with ours. For example, children born to parents who were exposed to ACEs had worse physical (Lê-Scherban et al, 2018; Madigan et al, 2017) and mental health (Madigan et al, 2017) as well as inferior socioemotional (McDonnell and Valentino, 2016) and developmental outcomes (Lê-Scherban et al, 2018; Madigan et al, 2017; Sun et al, 2017). Additional work outside ACEs has shown that offspring born to parents who experienced trauma such as genocide or indentured child labor during childhood also had higher risk for psychopathology (Field et al, 2011; Kuffer et al, 2016; Roth et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is a small but growing literature examining parent's trauma exposure during childhood and their offspring's health, but this work is situated in the ACE and genocide literatures. These studies have found that offspring born to parents with exposure to childhood trauma have lower levels of physical (Lê-Scherban et al, 2018; Madigan et al, 2017), socioemotional (McDonnell and Valentino, 2016), and mental health (Madigan et al, 2017) and inferior developmental outcomes (Sun et al, 2017). This begs the question of whether the traumatic experience from a parents' witnessing is sufficient on its own to impact health outcomes among offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the intergenerational impact of ACEs, which focuses on associations between parent ACEs and children's health, development, and functioning, has found continuity in risk of poor outcomes. 33 , 34 , 36 , 46 , 50 , 55 , 58 Thus, parent ACEs may contribute to chronic pain in youth, especially given their association with parent factors (eg, mental and physical health) that are implicated in pediatric chronic pain. 4 , 14 , 16 , 26 , 42 , 46 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies examined the impact of parental ACEs on children in the general population. Overall, parental ACEs seem to have a transgenerational relationship with developmental problems in their children [ 80 , 81 , 82 , 83 ]. More parental ACEs and less resilience have been found to be associated with parental coping difficulties [ 84 ].…”
Section: Introductionmentioning
confidence: 99%